Letrozole increases preantral follicle growth and decreases estradiol production without impairing follicle survival - Fukiko Kasuga-Yamashita; Tsuyoshi Baba; Sachiko Nagao; Yuya Fujibe; Miyuki Morishita; Yoshika Kuno; Tasuku Mariya; Hiroyuki Honnma; Toshiaki Endo; Tamotsu Kiya; Tsuyoshi Saito (BMC, 2022)
Abstract Background Letrozole has been reported to be effective in treating anovulation, preventing ovarian hyperstimulation syndrome (OHSS), and retrieving oocytes in breast cancer patients. However, the role and mechanism of letrozole in follicular development remain unclear. Results We treated mouse preantral follicles with various treatments; we found no significant difference in follicle survival rates in the letrozole (LET) group compared with the control group, but the average diameter of follicles in the LET group tended to be larger (CTRL vs. LET 30, p = 0.064; CTRL vs. LET 100, p = 0.025). The estradiol concentrations in culture media of the LET group were significantly lower than those observed in the control group (CTRL vs. LET 30, p = 0.038; CTRL vs. LET 100, p = 0.025). We further found a marked increase in follicle-stimulating hormone receptor (FSHR) gene expression in response to letrozole treatment (CTRL vs. LET 30, p = 0.075; CTRL vs. LET 100, p = 0.034). This result suggested that increased FSHR expression promotes follicle development. Letrozole inhibited aromatase activity, but the effect was limited. Letrozole did not significantly reduce vascular endothelial growth factor (VEGF) gene expression. Conclusions Letrozole may promote follicle development by increasing the expression of FSHR. Letrozole may be useful for fertility preservation of patients with estrogen-dependent cancers such as breast cancer and various other cancers. Whether letrozole has a direct effect in reducing OHSS requires further investigation.